Suicide mortality in India: a nationally representative survey - Patel, Vikram (Lancet, 2012)
BACKGROUND: There are few epidemiological studies of suicide in India. METHODS: A nationally representative mortality survey determined the cause of death occurring in 1·1 million homes in 6671 small areas chosen randomly from all parts of India. Two trained physicians independently assigned codes to the causes of death, based on a nonmedical surveyor’s field interview with household respondents. FINDINGS: About 3% of deaths at ages 15 years and older (2684/95 335) were due to suicide. This corresponds to about 187 000 suicide deaths in India in 2010 at these ages (115 000 men and 72 000 women; age-standardised rates per 100 000 at ages 15 years and older of 26·3 for men and 17·5 for women). For suicide deaths at ages 15 years and older 40% percent of male suicides and 56% of female suicides occurred at ages 15–29 years. A 15 year old in India had an approximate cumulative risk of 1·3% of dying before age 80 years by suicide; men had higher risk (1·7%) than women (1·0%), with especially high risks in South India (3·5% among men and 1·8% among women). Suicide risks were higher in educated versus illiterate adults. About half of the suicides were from poisoning, much of which was pesticide. At ages 15–29 years, suicide accounted for nearly as many deaths as transport accidents in men and maternal deaths in women. INTERPRETATION: Suicide death rates in India are amongst the highest in the world. A large proportion of suicides occur at younger ages, especially in women. Much of Indian suicides may be avoidable, starting with control of access to pesticides. FUNDING: U.S. National Institutes of Health